Pola Komunikasi Guru Agama kepada Siswa SMP Islam Plus Al Ruzhan Manonjaya dalam Pembinaan Akhlak - Sri Utami; Chairiawaty; Ahmad Siddiq, Asep (UNISBA Press, 2024)
Abstract. Communication is a relationship of direct contact and indirectly. Teachers and students are two things that cannot be separated, especially in moral development. In this study the authors took the title